PEMBANGUNAN MASYARAKAT MISKIN DI PEDESAAN PERSPEKTIF FUNGSIONALISME STRUKTURAL - Nikodemus - Niko; Yulasteriyani Yulasteriyani (MUHARRIK: Jurnal Dakwah dan Sosial, 2020)
Indonesia as a developing country continues to make improvements in the program and policy of quality of life and human resources development. The new vision of Indonesia’s president is 'SDM unggul Indonesia maju’ and this vision also applied by government today shows that the government is serious about improving human resources quality. The sustainable development program is the benchmark for how seriousness of this country performs evaluation and improvement for a fair and prosperous welfare of society. The pattern of community-based development has been integrated and structured into a challenge in the policy model of sustainable program. This paper focuses on the development issue of rural communities with critical to the thought of functional structural theories. The approach used is qualitative study of the library by using scientific research of both articles, journals, as well as related agency data. This paper explains that the social structure that occurs in rural communities, gives an unsubstantial impact on the development of the poor. Then, the development that is still on the functional structural is the benchmark in overcoming the reality of poverty in the rural community today. Nevertheless, the development of functional structural perspectives is still difficult to be contributed to the significance of Community welfare development. It is concluded that community development programs are still loaded with importance and vulnerable to being politicized by the elite.